2019
DOI: 10.1029/2019jb018056
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Data Assimilation of Cabled Ocean Bottom Pressure Records for the 2015 Torishima Volcanic Tsunami Earthquake

Abstract: Abnormal volcanic earthquakes occurring near the volcanic island of Torishima, south of Japan, sometimes generate relatively larger tsunamis compared to the seismic magnitudes. They have a non-double-couple focal mechanism known as compensated linear vector dipole. The unusual earthquake source mechanism poses difficulties in traditional tsunami forecasting method based on seismic parameters. Tsunami data assimilation, a method of tsunami forecast using offshore tsunami observation data and numerical model, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Since first introduced by Maeda et al (2015), a sequential tsunami data assimilation method has been of interest to many tsunami studies (e.g., Gusman et al, 2016; Mulia et al, 2017; Sheehan et al, 2019; Wang et al, 2019). The main intriguing feature of the method is that the tsunami forecasts can be computed without estimating its source, which can be very advantageous to nonseismic events including landslides.…”
Section: Possibility Of Assimilating Radar‐observed Velocitymentioning
confidence: 99%
“…Since first introduced by Maeda et al (2015), a sequential tsunami data assimilation method has been of interest to many tsunami studies (e.g., Gusman et al, 2016; Mulia et al, 2017; Sheehan et al, 2019; Wang et al, 2019). The main intriguing feature of the method is that the tsunami forecasts can be computed without estimating its source, which can be very advantageous to nonseismic events including landslides.…”
Section: Possibility Of Assimilating Radar‐observed Velocitymentioning
confidence: 99%
“…As long as the linearity is assumed, GFTDA is mathematically equivalent to the previous data assimilation approach. The application to the real data from the 2012 Haida Gwaii earthquake and the 2015 Torishima earthquake revealed that GFTDA achieved the same accuracy as the previous data assimilation approach while reducing the 99% calculation time required to issue a valid tsunami warning (Wang et al, 2017(Wang et al, , 2019c. Here, the accuracy is calculated by the geometric mean ratio of the observed and simulated tsunami amplitude.…”
Section: Improvement On Assimilation Speedmentioning
confidence: 88%
“…Heidarzadeh et al (2019) discussed the potential deployment of OBPGs in the western Mediterranean Sea based on data assimilation for a tsunami warning system and analyzed the sensitivity of the number and arrangement of stations. Wang et al (2019c) used the existing DONET observational network as an example to investigate the relationship between the number of observational stations used for assimilation and the forecasting accuracy. Yang et al (2019) conducted a synthetic 1-D experiment and found that the station interval of OBPGs should not exceed 50 km when using the optimal interpolation algorithm to guarantee satisfactory forecasting accuracy.…”
Section: Optimization Design Of Obpg Networkmentioning
confidence: 99%
“…For instance, S‐net stations provide a sampling rate of 0.1 s and are capable of detecting tsunamis with amplitudes of <1 cm (Kubota et al., 2020). Another OBPG network in Japan, the Dense Oceanfloor Network System for Earthquakes and Tsunamis, provide a sampling rate of 1 s and also can detect tsunamis with amplitudes of <1 cm (Kaneda, 2010; Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%